A systematic review of cell therapy modalities and outcomes in cerebral palsy - Akat, Ayberk; Karaoz, Erdal (SPRINGER, 2025)
Cerebral palsy is widely recognized as a condition that results in significant physical and cognitive disabilities. Interventions aim to improve the quality of life and reduce disability. Despite numerous treatments and significant advancements, cerebral palsy remains incurable due to its diverse origins. This review evaluated clinical trials, studies, and case reports on various cell therapy approaches for cerebral palsy. It assessed the clinical outcomes of applying different cell types, including mesenchymal stem cells, olfactory ensheathing cells, neural stem/progenitor cells, macrophages, and mononuclear cells derived from peripheral blood, cord blood, and bone marrow. In 60 studies involving 1474 CP patients, six major adverse events (0.41%) and 485 mild adverse events (32.9%) were reported. Favorable therapeutic effects were observed in 54 out of 60 cell therapy trials, indicating a promising potential for cell treatments in cerebral palsy. Intrathecal MSC and BM-MNC applications revealed therapeutic benefits, with MSC studies being generally safer than other cell therapies. However, MSC and BM-MNC trials have shown inconsistent results, with some demonstrating superior efficacy for certain outcomes. Cell dosage, transplantation route, and frequency of administration can affect the efficacy of these therapies. Our findings highlight the promise of cell therapies for improving cerebral palsy treatment and stress the need for ongoing research to refine treatment protocols and enhance safety. To establish conclusive evidence on the comparative effectiveness of various cell types in treating cerebral palsy, randomized, double-blind clinical trials are essential.
Keywords: Cerebral palsy; Cell therapy; Clinical trials; Regenerative medicine; UMBILICAL-CORD BLOOD; MESENCHYMAL STEM-CELLS; BONE-MARROW; MONONUCLEAR-CELLS; NEUROLOGICAL DISORDERS; MOTOR FUNCTION; STROMAL CELLS; CHILDREN; TRANSPLANTATION; INFUSION; Cell Biology